2022
DOI: 10.1038/s41591-022-01973-2
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Proof studies: assessing the evidence of risk

Abstract: Exposure to risks throughout life results in a wide variety of outcomes. Objectively judging the relative impact of these risks on personal and population health is fundamental to individual survival and societal prosperity. Existing mechanisms to quantify and rank the magnitude of these myriad effects and the uncertainty in their estimation are largely subjective, leaving room for interpretation that can fuel academic controversy and add to confusion when communicating risk. We present a new suite of meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(117 citation statements)
references
References 41 publications
4
110
0
3
Order By: Relevance
“…We evaluated the relationship between unprocessed red meat consumption and six selected disease outcomes following implementation of a meta-analytic approach 20 . We found that unprocessed red meat intake had weak evidence of an association with increased risk of colorectal cancer, breast cancer, IHD and type 2 diabetes and no evidence of an association with ischemic stroke and hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We evaluated the relationship between unprocessed red meat consumption and six selected disease outcomes following implementation of a meta-analytic approach 20 . We found that unprocessed red meat intake had weak evidence of an association with increased risk of colorectal cancer, breast cancer, IHD and type 2 diabetes and no evidence of an association with ischemic stroke and hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the star rating categories 20 , unprocessed red meat and colorectal cancer, breast cancer, IHD and type 2 diabetes are all two-star pairs, whereas the two stroke causes are one-star pairs. These star ratings reflect both the magnitude of the RR and its uncertainty and offer policy makers a simple way to conceptualize and compare the evidence for an association between risk and outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations